Bone changes in congenital cytomegalic inclusion disease. Issue 2 (February 1975) - McCandless, A E; Davis, C; Hall, E G
Abstract : 1. While below 10 degrees C, the initial burst of Pi liberation in the hydrolysis of Mn(II)-ATP by heavy meromyosin or myosin subfragment 1 was inhibited by the pre-addition of ADP without any change in the steady-state activity, it was not inhibited above 10 degrees C. The burst size was about one mole per two moles of myosin active sites. 2. Above 10 degrees C, the ultraviolet absorption spectrum of heavy meromyosin induced by ATP in MnC12 was similar to that induced in MgC12 and the spectral decay to the ADP-induced level occurred only after all the ATP in the solution was depleted. In contrast, below 10 degrees C the spectrum induced by ATP in MnC12 decayed to the ADP- induced level within a few seconds after the addition of ATP, although ATP was present in the solution. 3. These two results indicate that in Mn-ATP above 10 degrees C at the burst site there is a myosin*-ADP-Pi complex generated by ATP hydrolysis while below 10 degrees C there is a myosin-produce tocplex identical with the one generated by adding ADP (and Pi) to myosin. 4. At tempertures both above and below 10 degrees C, the Mn-ATP hydrolysis of heavy meromyosin was activated by actin and superprecipitation of actomyosin occurred. Characteristics of these phenomena showed a transition at around 10 degrees C.